2019
DOI: 10.1002/dta.2713
|View full text |Cite
|
Sign up to set email alerts
|

A possible new oxidation marker for hair adulteration: Detection of PTeCA (1H‐pyrrole‐2,3,4,5‐tetracarboxylic acid) in bleached hair

Abstract: Hair analysis has become a valuable tool in forensic toxicology to assess drug or alcohol abstinence. Yet, hair adulteration by cosmetic products presents a major challenge for forensic hair analysis. Oxidative treatments, e.g. bleaching, may lead to analyte loss and thereby to false negative results. Currently, the eumelanin degradation product 1H-pyrrole-2,3,5-tricarboxylic acid (PTCA) serves as a marker for oxidative hair treatment, but requires the definition of cut-off values. To investigate further eumel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…34 Through oxidation processes or UVA-induced photoaging, it can be degraded by oxidation and/or cross-linking of its indole-moieties. [35][36][37] In line with previous work, 13,14 the applied untargeted workflow allowed for the detection of the eumelanin degradation products PTCA, 1H-pyrrole-2,3,4-tricarboxylic acid (isoPTCA) and PTeCA either as significantly increased (PTCA, isoPTCA) or as newlyformed (PTeCA) after bleaching. 13,14 This consistence proofs the general applicability of the current untargeted workflow to detect potential markers for oxidative hair treatment.…”
Section: Marker Interpretationsupporting
confidence: 62%
See 2 more Smart Citations
“…34 Through oxidation processes or UVA-induced photoaging, it can be degraded by oxidation and/or cross-linking of its indole-moieties. [35][36][37] In line with previous work, 13,14 the applied untargeted workflow allowed for the detection of the eumelanin degradation products PTCA, 1H-pyrrole-2,3,4-tricarboxylic acid (isoPTCA) and PTeCA either as significantly increased (PTCA, isoPTCA) or as newlyformed (PTeCA) after bleaching. 13,14 This consistence proofs the general applicability of the current untargeted workflow to detect potential markers for oxidative hair treatment.…”
Section: Marker Interpretationsupporting
confidence: 62%
“…Screening for potential differing metabolites due to oxidative hair treatment was performed with a previous evaluated LC-HRMS method. 14,20 To avoid errors resulting from varying instrument performances over time, all samples were analyzed in randomized order and direct comparison of sample results was only performed within one batch. The analytical performance and the reproducibility of the batch analyses were monitored by deviation of RT and peak areas in SST and pooled QC samples.…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this study, we could show that the hair metabolome depends on the hair color and changes along the hair strand in an entirely natural way. Additionally, it has been shown that cosmetic hair treatments significantly affect the detectability of endogenous compounds [ 6 , 18 , 19 ]. These aspects are not considered in published hair metabolomic studies so far, which highlights the urgent need to raise attention to this topic.…”
Section: Resultsmentioning
confidence: 99%
“…Besides conventional GC-or LC-MS methods, LC-HRMS was established particularly for untargeted metabolomics studies, again because of its high specificity, sensitivity, and flexibility [58][59][60][61][62][63]. There are two main application fields, one focusing on the change of the endogenous compounds under the influence of drug administration [62,[64][65][66][67][68][69] or sample manipulation [65,[70][71][72][73][74] and one on the use of metabolomics techniques for investigating the metabolism of new drugs, namely of NPS [60,61,75]. Metabolomics could also play a role in doping control, e.g., for detecting hormone abuse considering that hormones have a strong influence on human endogenous metabolism changing several endogenous parameters [76].…”
Section: Metabolomics Techniques In Analytical Toxicologymentioning
confidence: 99%